Determination of phenolic contents and antioxidant activity test of ethanol extract of Sirih merah (Piper crocatum Ruiz & Pav.) leaves using the DPPH method - Kasta Gurning; Sifikal Lumbangaol; Risanti F. R Situmorang; Saronom Silaban (Jurnal Pendidikan Kimia (JPKim), 2021)
The research objectives were to identify the secondary metabolite components, total phenolic content and determine the antioxidant activity of the ethanol extract of red betel leaf (Piper crocatum Ruiz & Pav.). The extraction process was carried out by materation using ethanol as a solvent. Determination of total phenolic content was carried out colorimetrically with Folin-Ciocalteu reagent measured at a maximum wavelength of 765 nm. Determination of antioxidant activity using the DPPH method measured by spectrophotometry at a maximum wavelength of 517 nm. The results of phytochemical screening of the ethanolic extract of red betel leaf contain secondary metabolites, including flavonoid, phenolic, tannin, alkaloids, steroids, and triterpenoids. The total phenolic content of the red betel leaf ethanol extract was 0.949±0.003 mg GAE/g d.w. and has antioxidant activity (IC50) 84,656 including strong category as an antioxidant. Keywords: Piper crocatum Ruiz & Pav., Antioxidant, Ethanol extract, Folin-Ciocalteu and DPPH